PROFESIONALISME GURU BERBASIS NILAI-NILAI RELIGIUS DAN AKHLAK MULIA - Qomar, Mujamil (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2016)
Profession, professional, and professionalism are the three words that have different editors and with different emphases, but the same substance. These three words are used in the elaboration of the position of teachers PAI. All three of understanding the existence of a work performed by the expertise, so that the three important especially in performing work involving other people in an educational institution. The teacher's role is not limited to the transfer function of knowledge to students, but teachers have a wider role in the community to creating value changes.Changes in the value of the community showed the competence of teachers able to encourage their learning interactions. The teaching profession is able to provide a strong impetus values and can convey information and knowledge to the learners. It is the responsibility inherent to each educator. Educator is the predicate in charge of implementing keteladan-based learning and religious values. The aspect of responsibility. Another thing is the issue of competence. PAI teacher competence was actually the heaviest and most complex than teachers in addition to PAI. Because the material PAI includes the disciplines of theology (tawhid), the science of morals, the science of the Koran, the science of hadith, the science of fiqh, the science of the history of Islamic culture and the Arabic language. Indeed, the Arabic language is not included in the components of PAI, but the Arabic language as a tool of science is always attached to the PAI. One can not possibly master the material PAI without the ability to master the Arabic language.